2020
DOI: 10.1186/s13227-020-00155-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors underlying wing margin color patterns and pupal cuticle markings in butterflies

Abstract: Background The diversity of butterfly color patterns can be attributed to a relatively small number of pattern elements that are homologous across Lepidoptera. Although genes involved in patterning some of these elements have been identified, the development of several major elements remains poorly understood. To identify genes underlying wing pupal cuticle markings and wing margin color patterns, we examined expression of the candidate transcription factors Engrailed/Invected (En/Inv), Distal-less (Dll), Cubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Previous studies have shown that expression of both Dll and Sal proteins also correlate with patterns of different colour states on the wing. In 16-24h pupal wings, expression of Sal protein spatially maps to pale-colored non-eyespot marginal wing patterns of nymphalids (Reed et al, 2020) while both Dll and Sal proteins are expressed in silver scales along the wing margin in the lycaenid butterfly, Lycaeides melissa (Brunetti et al, 2001). Thus, both Dll and sal may be ancestral pattern organisers working within the distal part of the wing, operating independently of melanic fate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that expression of both Dll and Sal proteins also correlate with patterns of different colour states on the wing. In 16-24h pupal wings, expression of Sal protein spatially maps to pale-colored non-eyespot marginal wing patterns of nymphalids (Reed et al, 2020) while both Dll and Sal proteins are expressed in silver scales along the wing margin in the lycaenid butterfly, Lycaeides melissa (Brunetti et al, 2001). Thus, both Dll and sal may be ancestral pattern organisers working within the distal part of the wing, operating independently of melanic fate.…”
Section: Discussionmentioning
confidence: 99%
“…In late larval wing discs of B. anynana , both Dll (green) and sal (orange) are co-expressed at high levels in the center of eyespots (Reed et al, 2020). However, in late larval wing discs of P. canidia, Dll and sal are not expressed in spot centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations